DETERMINANTS DE LA SOUS-ALIMENTATION DES MENAGES EN CÔTE D’IVOIRE : CAS DES REGIONS CENTRE ET CENTRE-EST - Yabile, Kinimo Rene (European Scientific Journal, ESJ, 2013)
Undernutrition is one of the major issues in the development agenda; the increase in food prices in recent years increases the vulnerability of households and climate change has adverse impacts on agricultural production. The objective of this study is to identify the determinants of undernutrition households in the Central and East-Central Côte d’Ivoire, ranked among the most deprived areas. Using data from the Survey of Household Living Standards (ENV 2002), Logit econometric models revealed that among these factors include household size, gender of household head, education level of the head household, the main occupation of the household head, the industry, living environment and the practice of farming. This analysis shows that the undernourished households are characterized in particular by high size, low level of education, the exercise of the profession of craftsman in the informal sector and are mostly headed by women. These determinants are levers that authorities may rely to reduce undernutrition. Therefore, it is desirable for the government to popularize family planning (reduction in household size), raising the level of education of the population at least at the secondary level, to promote the profession of craftsman by the capacity building and stakeholder access to microfinance to combat undernutrition.